Quantum Ethics: Navigating the Intersection of Quantum Mechanics and Metaethics in the Digital Era for a Just and Equitable Society - Damayanti, Cicilia (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
The advancement of quantum technologies and their integration with digital systems has resulted in enormous changes in society, providing new opportunities for furthering subjects such as artificial intelligence, the internet of things (IoT), and quantum computing. The ethical ramifications of these technologies, however, have not been adequately investigated, raising worries about their possible harmful influence on society. This research examines the convergence of quantum physics, metaethics, and the digital era in order to determine the implications of these technologies and to offer ethical frameworks for maintaining a just and equitable society. It will analyse the obstacles faced by the employment of quantum technologies in the digital era, including concerns relating to privacy, security, and the possibility for biased decision-making, through a thorough analysis of relevant literature. It then investigates the possibilities of multidisciplinary approaches that combine quantum mechanics and metaethics principles to overcome these issues and construct ethical frameworks that emphasize human values. The report suggests that a comprehensive strategy that prioritizes ethical issues is critical for the development of quantum technologies in the digital era. This necessitates a coordinated effort among stakeholders from many sectors such as technology, ethics, policy, and governance. The article provides a complete ethical framework that incorporates quantum mechanics and metaethics principles to ensure that the advantages of new technologies are realized while limiting any negative consequences.